Identités translationnelles et perspectives postcoloniales: Транслациони идентитети и постколонијални перспективи - Angelovska, Despina (Identities: Journal for Politics, Gender and Culture, 2006)
Author(s): Despina Angelovska | Деспина Ангеловска Title (French): Identités translationnelles et perspectives postcoloniales Title (Macedonian): Транслациони идентитети и постколонијални перспективи Translated by (French to Macedonian): Despina Angelovska | Деспина Ангеловска Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 5, No. 2 (Summer 2006) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 117-142 Page Count: 25 Citation (French): Despina Angelovska, “Identités translationnelles et perspectives postcoloniales,” Identities: Journal for Politics, Gender and Culture, Vol. 5, No. 2 (Summer 2006): 117-142. Citation (Macedonian): Деспина Ангеловска, „Транслациони идентитети и постколонијални перспективи“, Идентитети: списание за политика, род и култура, т. 5, бр. 2 (лето 2006): 117-142.